Candidaemia in Sweden: a nationwide prospective observational survey. (17th January 2013) - Ericsson, J.; Chryssanthou, E.; Klingspor, L.; Johansson, A. G.; Ljungman, P.; Svensson, E.; Sjölin, J.; Roilides, E.
Abstract A prospective observational nationwide investigation was performed from September 2005 to August 2006 to study the epidemiology of candidaemia in Sweden. From 385 patients, 403 isolates were recovered, yielding an incidence of 4.2 cases per 100 000 inhabitants. Candida albicans was the most common species (61%), followed by Candida glabrata (20%) and Candida parapsilosis (9%). The rates of resistance to fluconazole were ≤1% in C. albicans and 6–29% in non‐albicans species other than C. glabrata and Candida krusei. Resistance to voriconazole was rare, except for C. glabrata and C. krusei. Only three isolates had reduced susceptibility to amphotericin B, and one had reduced susceptibility to caspofungin.